WHO VOTES EXPRESSIVELY, AND WHY? EXPERIMENTAL EVIDENCE. (18th August 2014) - Etang, Alvin; Fielding, David; Knowles, Stephen
ABSTRACT: Experiments have shown that some people behave more altruistically in collective decisions than they do in individual ones, which could be interpreted as an 'expressive voting' effect. However, there is substantial variation in the behaviour of experimental participants. We conduct experiments to explore the reasons for this variation, and find that certain characteristics are sometimes associated with a propensity for expressive voting. However, the strength of these effects depends on the ordering of individual and collective choices. The 'warm glow' of expressive voting can influence subsequent individual decisions, and the 'cold shower' of individual selfishness can influence subsequent collective decisions.